Mathematical Foundations for Social Computing - Chen, Yiling; Ghosh, Arpita; Kearns, Michael; Roughgarden, Tim; Vaughan, Jennifer Wortman (Communications of the ACM, 2016)
Social computing encompasses the mechanisms through which people interact with computational systems: crowdsourcing systems, ranking and recommendation systems, online prediction markets, citizen science projects, and collaboratively edited wikis, to name a few. These systems share the common feature that humans are active participants, making choices that determine the input to, and therefore the output of, the system. The output of these systems can be viewed as a joint computation between machine and human, and can be richer than what either could produce alone. The term social computing is often used as a synonym for several related areas, such as "human computation" and subsets of "collective intelligence;" we use it in its broadest sense to encompass all of these things.